OTHR-05. THE ABILITY TO MAKE INFORMED TREATMENT DECISIONS IS COMPROMISED IN ADULTS WITH ADVANCED STAGE CANCER. (12th August 2019) - Triebel, Kristen; Mulhauser, Kyler; Gammon, Meredith; Gerstenecker, Adam; Nabors, L Burt; Fiveash, John
Abstract: OBJECTIVE: To investigate medical decision-making capacity (MDC) in patients with advanced stage cancer. METHODS: Participants were 113 newly diagnosed adults with brain metastases and 41 adults with metastatic cancer without brain metastases who were recruited from an academic medical center and 40 demographically-matched healthy controls recruited from the community. We evaluated MDC using the Capacity to Consent to Treatment Instrument (CCTI) Vignette B and its four clinically relevant consent standards (expressing a treatment choice, appreciation, reasoning, and understanding). Capacity impairment ratings (no impairment, mild/moderate impairment, and severe impairment) on the consent standards were also assigned to each participant using cutoff scores derived statistically from the performance of the control group. RESULTS: Both of the metastatic cancer groups (with and without brain metastasis) performed significantly below controls on consent standards of understanding and reasoning. The brain metastasis group performed below the non-metastatic cancer group on understanding. Capacity compromise was defined as performance ≤1.5 standard deviations (SD) below the control group mean. Using this definition, approximately 65% of the participants with brain metastases and 51% of participants with metastatic cancer without brain metastases were impaired on at least one MDC standard. CONCLUSION: Over half of participants with metastatic cancer regardless of whether they have brain disease have reduced capacity to make treatment decisions. The finding of impaired MDC in patients without brain metastases is surprising and suggests this group likely exhibits cognitive deficits that impact their ability to understand and reason about different treatment options. The reasons underlying this impairment will be investigated. This highlights the importance of routine clinical assessment of MDC in all patients with metastatic cancer when important treatment decisions are being discussed. These results also indicate a need for the development and investigation of interventions to support or improve MDC in this patient population.